Análise multicritério dos principais indicadores de um aeroporto hub no nordeste: aplicação do método analytical hierarchy process - Moura, Ingrid Rebouças de (Universidade Federal Rural do Semi-Árido, 2019)
Currently, the civil aviation industry enjoys high-speed development and is receiving increasing attention with increasing travel networks are changing and hub and spoke wheels are increasingly desired by airports. In the choice of an airport hub by an airline are several benefits related to the movement of passengers, which implies a detailed study of the demand, geographic location and airport infrastructure available to accommodate this new model of flight operations. In this sense, this work aims to carry out a multicriteria study on the main characteristics for an airport to establish itself as a hub, establishing the importance that one component has over another as a system installation factor. In this way, this research is directed the recent news of the choice of hub of the airline Latam Airlines Brasil, which intends to bring a connection of flights to the Nordeste region. The company reports difficulties in deciding between the airports of Fortaleza, Natal and Recife. With the help of secondary sources and the opinion of specialists in the area of operations, these airports were quantified according to the indicators analyzed, and through a methodology based on the use of the Analytical Hierarchy Process (AHP), it was possible to determine the relevance of the components and the choice of airport in the Nordeste that would be better able to receive the Latam hub.
Keywords: Aeroportos; Hub and spoke; AHP; Nordeste; Airports; Hub and spoke; AHP; Nordeste; ENGENHARIAS::ENGENHARIA CIVIL